Perbandingan Mutu Dan Harga Tablet Amoksisilin 500 Mg Generik Dengan Non Generik Yang Beredar Di Pasaran - Harianto, Harianto; W, Sabarijah; Transitawuri, Fitri (Majalah Ilmu Kefarmasian, 2006)
Amoxiciilin is an antibiotic of penicillin. It has been used to treat bacterial infections that caused by Gram negative bacteria and Gram positive bacteria. Most of amoxicillin tablet has been sold with generic name and non generic name. This research was proposed to compare quality and price of amoxicillin tablet 500 mg at the drug store. Especially, for amoxicillin tablet 500 mg generic and non generic. Determination of quality amoxicillin tablet could be showed from standard quality of amoxicillin tablet was based at USP XXVI. Identification, dissolution and assay were included standard quality of amoxicillin tablet. Identification test was performed by TLC with mobile phase consist of methanol, chloroform, water and pyridine (90:80:30:10). Assay of dissolution test was performed by HPLC with mobile phase potassium dihydrogen phosphate buffer and acetonitrile (39:1). Assay of tablet was performed by HPLC with mobile phase potassium dihydrogen phosphate buffer and acetonitrile (96:4). The experiment was held to 15 brands of tablet which they had consisted 3 brands of generic tablet and 12 brands of non generic tablet. The test resulted that every brands of tablet fulfilled standard quality of amoxicillin tablet. But in the test, there was variation of price, in ordinarily price of non generic tablet was more expensive than generic tablet.